2017
DOI: 10.1016/j.neuropharm.2017.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor 2 inhibits thalamically-driven glutamate and dopamine release in the dorsal striatum

Abstract: The striatum plays critical roles in action control and cognition, and activity of striatal neurons is driven by glutamatergic input. Inhibition of glutamatergic inputs to projection neurons and interneurons of the striatum by presynaptic G protein-coupled receptors (GPCRs) stands to modulate striatal output and striatum-dependent behaviors. Despite knowledge that a substantial number of glutamatergic inputs to striatal neurons originate in the thalamus, most electrophysiological studies assessing GPCR modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 56 publications
4
36
0
Order By: Relevance
“…Our findings add to the limited knowledge of the intracellular signaling pathways regulating the thalamostriatal system, in particular the molecular mechanisms underlying synaptic depression of thalamo-dSPN synapses (Atwood et al, 2014;Ellender et al, 2011;Johnson et al, 2017;Parker et al, 2016;Wu et al, 2015). t-LTD at thalamostriatal inputs has been shown to be independent of eCBs released from the postsynaptic SPN (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our findings add to the limited knowledge of the intracellular signaling pathways regulating the thalamostriatal system, in particular the molecular mechanisms underlying synaptic depression of thalamo-dSPN synapses (Atwood et al, 2014;Ellender et al, 2011;Johnson et al, 2017;Parker et al, 2016;Wu et al, 2015). t-LTD at thalamostriatal inputs has been shown to be independent of eCBs released from the postsynaptic SPN (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…In this experimental setting, the STDP protocol failed to induce significant changes in o-EPSP Ctx (98% ± 8% of baseline, n = 7, p > 0.05; Figure 4C), even when applied in the presence of RS39604 (5 mM; 92% ± 6% of baseline, n = 8, p > 0.05; Figure 4C). To corroborate this lack of involvement of corticostriatal synapses in a second model, we injected an adeno-associated viral (AAV) vector encoding ChR2-eYFP under the control of the CaMKIIa promoter [rAAV5-CaMKIIa-ChR2(H134R)-eYFP] into the M1 motor cortex region of C57BL/6J mice (Johnson et al, 2017) ( Figure S6A). As with Thy1-ChR2 mice ( Figure 4C), the STDP protocols failed to induce significant changes in dSPNs o-EPSP Ctx , regardless of the presence or absence of RS39604 (dSPN Ctx , 97% ± 6% of baseline, n = 7, p > 0.05; dSPN Ctx + RS39604, 90% ± 2% of baseline, n = 6, p > 0.05; dSPN Ctx versus dSPN Ctx + RS39604, p = 0.7 Mann Whitney test; Figures S6B and S6C).…”
Section: -Ht Signaling Controls T-ltd At Thalamic Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, slow EPSCs in ldStr ChIs are reliably evoked with single spikes, at low frequency, suggesting that mGluR1 receptors are closer to synaptic release sites in ChIs than in Purkinje cells or DA neurons. ChIs, as well as SPNs, express both mGluR1 and iGluRs, and iGluR responses are evoked in SPNs by stimulation of other glutamate inputs ( Ding et al, 2010 ; Johnson et al, 2017 ), but not mGluR1 responses. Furthermore, mGluR1 is not enriched in ChIs.…”
Section: Discussionmentioning
confidence: 99%
“…Doses of Amisulpride between 600-900 mg/day give occupancy rate D2 of 70-80%, while the doses >1100 mg/ day give occupancy rate D2 of >85%, and at these higher doses may be observed EPS. Blocking the receptors 5HT2A and preferential blocking certain subtypes of dopamine receptors it was an assumption relevant in defining the mechanism effectiveness atypical or second generation antipsychotics in the treatment of negative symptoms [7]. The studies PET of atypical antipsychotics showed an extended of the receptors occupancy rate 5HT2A in the cerebral cortex clozapine, olanzapine, risperidone and quetiapine, but not amisulpride.…”
mentioning
confidence: 99%